The modulatory role of sulfated and non-sulfated small molecule heparan sulfate-glycomimetics in endothelial dysfunction: absolute structural clarification, molecular docking and simulated dynamics, SAR analyses and ADMET studies - Gill, Daniel M.; Povinelli, Ana Paula R. [UNESP]; Zazeri, Gabriel [UNESP]; Shamir, Sabrina A.; Mahmoud, Ayman M.; Wilkinson, Fiona L.; Alexander, M. Yvonne; Cornelio, Marinonio L. [UNESP]; Jones, Alan M. (Royal Soc Chemistry, 2021)
The conceptual technology of small molecule glycomimetics, exemplified by compounds C1-4, has shown promising protective effects against lipid-induced endothelial dysfunction, restorative effects on diabetic endothelial colony forming cells, and preventative effects on downstream vascular calcification amongst other important in vitro and ex vivo studies. We report the optimised synthesis of an array of 17 small molecule glycomimetics, including the regio-, enantio- and diastereo-meric sulfated scaffolds of a hit structure along with novel desulfated examples. For the first time, the absolute stereochemical configurations of C1-4 have been clarified based on an identified and consistent anomaly with the Sharpless asymmetric dihydroxylation reaction. We have investigated the role and importance of sulfation pattern, location, regioisomers, and spatial orientation of distal sulfate groups on the modulation of endothelial dysfunction through their interaction with hepatocyte growth factor (HGF). In silico studies demonstrated the key interactions the persulfated glycomimetics make with HGF and revealed the importance of both sulfate density and positioning (both point chirality and vector) to biological activity. In vitro biological data of the most efficient binding motifs, along with desulfated comparators, support the modulatory effects of sulfated small molecule glycomimetics in the downstream signaling cascade of endothelial dysfunction. In vitro absorption, distribution, metabolism, elimination and toxicity (ADMET) data demonstrate the glycomimetic approach to be a promising approach for hit-to-lead studies.